A real-world disproportionality analysis of FDA adverse event reporting system (FAERS) events for lecanemab - Yan, Linlin; Zhang, Linhai; Xu, Zucai; Luo, Zhong (Frontiers in Pharmacology, 2025)
BackgroundLecanemab is a humanized murine IgG1 antibody. Recent Phase 3 clinical trials have demonstrated its ability to reduce brain amyloid-β (Aβ) load and slow cognitive decline in patients with early Alzheimer’s disease (AD). However, since its approval, reports on adverse effects (AEs) associated with lecanemab have been limited. To better understand the AEs related to lecanemab and provide guidance for future clinical use, we analyzed lecanemab-associated AEs using data from the United States Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS).MethodsWe extracted all AEs reports from the FAERS database for the period from the first quarter of 2023 to the third quarter of 2024. Using the Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and Multi-item Gamma Poisson Shrinker (MGPS) algorithms, we conducted a comprehensive analysis of lecanemab-related AEs, restricting the analysis to AEs with the role code of primary suspect (PS).ResultsA total of 811 AEs reports related to lecanemab used in AD patients and 506 AEs in Non-AD patients were included. The preferred terms (PTs) identified as positive across all four algorithms included headache, Amyloid Related Imaging Abnormalities-oedema/effusion (ARIA-E), chills, Amyloid Related Imaging Abnormalities-haemosiderosis/microhaemorrhage (ARIA-H), fatigue, infusion-related reaction, nausea, pyrexia, pain, influenza like illness, and so on. Among these, ARIA-E, ARIA-H, brain oedema and status epilepticus were associated with Important Medical Events (IMEs) for AD patients, and brain oedema, cerebral haemorrhage, cerebral microhaemorrhage, subdural haematoma, ischaemic stroke, cerebral infarction were associated with IMEs for Non-AD patients. At the system organ class (SOC) level, the highest signal detection for lecanemab was observed in nervous system disorders among AD and Non-AD patients [ROR for AD: 2.42 (2.2–2.65); ROR for Non-AD: 6.97 (6.12–7.95)]. The median time to the occurrence of these AEs was 44 days after administration in AD patients and 30 days for Non-AD patients.ConclusionThis study utilized the FAERS database to evaluate lecanemab-associated AEs in AD and non-AD patients, along with their temporal patterns post-marketing authorization, thereby establishing a foundation for subsequent clinical pharmacovigilance. A biweekly 10 mg/kg was identified as the optimal therapeutic dosage. ARIA emerged as frequent treatment-related AEs, with APOEɛ4 carriers demonstrating heightened susceptibility. This necessitates serial brain MRI surveillance for all patients during treatment, aimed not only at early ARIA detection but also vigilant monitoring of IMEs including cerebral haemorrhage, cerebral microhaemorrhages, subdural haematoma, cerebral edema, ischaemic stroke, and cerebral infarction. While AD patients predominantly exhibited non-specific clinical manifestations, non-AD cohorts showed elevated risks of stroke-related complications. Consequently, dynamic neurological deficit monitoring is indispensable for non-AD populations receiving lecanemab to mitigate adverse outcomes. Finally, comprehensive reassessment of anticoagulant or antiplatelet therapy indications is warranted in both AD and non-AD patients to reduce hemorrhagic risks.